2018
DOI: 10.1080/02699931.2017.1423280
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotional cues on prospective memory: a systematic review with meta-analyses

Abstract: Remembering to perform a behaviour in the future, prospective memory, is essential to ensuring that people fulfil their intentions. Prospective memory involves committing to memory a cue to action (encoding), and later recognising and acting upon the cue in the environment (retrieval). Prospective memory performance is believed to be influenced by the emotionality of the cues, however the literature is fragmented and inconsistent. We conducted a systematic search to synthesise research on the influence of emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 82 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…Communication strategies could utilize positive cues to action, including encouragement from loved ones and trusted figures such as physicians and religious leaders, sharing personal stories, and peer pressure [125]. Studies also have shown social expectation and portraying anticipated regret from inaction to be potential motivators for vaccination [104,126].…”
Section: Discussionmentioning
confidence: 99%
“…Communication strategies could utilize positive cues to action, including encouragement from loved ones and trusted figures such as physicians and religious leaders, sharing personal stories, and peer pressure [125]. Studies also have shown social expectation and portraying anticipated regret from inaction to be potential motivators for vaccination [104,126].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, it may seem plausible to attribute this prospective-memory advantage to general effects of emotional valence. However, the effects of emotional manipulations on prospective memory are heterogenous (Hostler et al, 2018), with some studies showing positive effects of emotion on prospective memory (e.g., May et al, 2015), whereas others show negative effects (e.g., Clark-Foos et al, 2009). In Experiment 3, a different manipulation of emotional valence (descriptions of disgusting, pleasant, and neutral behaviors) had, somewhat surprisingly, no effect on prospective memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, such an explanation is complicated by the fact that emotion can also have adverse effects on prospective memory (Clark-Foos et al, 2009). According to a recent meta-analysis (Hostler et al, 2018), the effects of emotional stimuli on prospective memory are heterogenous, differ for positive and negative valence, and are characterized by complex interactions with other variables. Furthermore, it is unclear whether these findings generalize to the present paradigm because most studies used materials with established emotional valence (e.g., emotional words), whereas in our Experiments 1 and 2, we used a priori neutral materials (neutral faces) that acquired positive or negative valence through their association with the social interactions (cooperative or cheating behavior).…”
Section: Methodsmentioning
confidence: 99%
“…To further understand which aspects of controlled processes are targeted by cue salience during adolescence, it might be important to systematically manipulate complexity and cognitive demands. In addition, manipulations around cue-salience that align with adolescent sensitivities (such as socio-emotional processes) might be an interesting route going forward, especially since positively-valenced cues have been shown to improve prospective memory in adults (Altgassen et al, 2010;Hostler et al, 2018).…”
Section: Age-related Differencesmentioning
confidence: 99%